PERUBAHAN ALOKASI ANGGARAN DANA DESA TERHADAP PENCEGAHAN COVID-19 DI KECAMATAN MOYO HULU - Saleh, Muhammad; Trishuta Pathiassana, Mega; Faturrahman, Fadli (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2020)
The current world disaster phenomenon has had an impact on the countryIndonesia. This can be seen from the paralysis of the community's economy both in the fieldgovernment and private. With the Covid-19 Virus that resultedparalysis on every front that requires the government to shift allocationsexisting funds both at the central and regional levels. This research aims to seechanges in village fund budget allocations for the prevention of Covid-19 in sub-districtsMoyo Hulu. The village that is the object of observation in Moyo Hulu sub-district is the villageSemamung, Pernek village, and Leseng village. The type of research used inThis research is a qualitative research, using an interpretive paradigm.The results of this study indicate that budget planning has been carried out based on principlesgood governance, namely transparent and accountable Village Fund Management so farrunning effectively, can be seen concrete evidence, namely in the form of developmentinfrastructure, community empowerment. Changes in Village funds due to Covid-19 toohas complied with the regulations that overshadow it.